2004
DOI: 10.1038/sj.bjc.6601464
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral germ-cell tumours: 22-year experience at the Institut Gustave Roussy

Abstract: The aim of this study was to describe the incidence, clinical and histological characteristics, treatment and long-term follow-up of bilateral germ-cell tumours (BGCT) of the testis in order to determine in what respects they differ significantly from unilateral germcell tumours. In all, 31 patients with BGCT had metachronous tumours and 14 had synchronous tumours. Among the metachronous tumours, 61% occurred more than 5 years after the first tumour. The overall incidence of BGCT in patients with testicular ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 44 publications
1
33
0
2
Order By: Relevance
“…Noteworthy, 20–30% of all sequential bilateral testicular tumors arise despite chemotherapy for the primary tumor [17,18,19]. That observation is another strong indication for the imperfect efficacy of chemotherapy on TIN.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, 20–30% of all sequential bilateral testicular tumors arise despite chemotherapy for the primary tumor [17,18,19]. That observation is another strong indication for the imperfect efficacy of chemotherapy on TIN.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bilateral testis tumors (simultaneous or sequential) occur in 1% to 5% of all testicular cancers. [2][3][4] In these circumstances the current standard surgical treatment is bilateral orchiectomy, which has a negative impact on quality of life because it results in permanent azoospermia and the lifelong need for androgen replacement. To avoid androgen deficiency and sterility conservative surgery of the testis has been recently promoted by several groups.…”
mentioning
confidence: 99%
“…3,4,5 Of these relapses, both were in the contralateral testicle, with an overall incidence of 4% (3 of 75) for bilateral testis involvement, similar to the reported incidence of 1% to 3.2%. 10,11 Table 5 compares the results of this study with large prospective and retrospective studies of both surveillance and adjuvant radiation in stage I seminoma. In a study of prognostic factors for relapse in early stage seminoma, Warde et al showed a significant relationship between age and risk of relapse, with patients younger than 34 years having a significantly increased risk of relapse compared with patients 34 years of age or older (21% vs. 9%, P Ͻ 0.009).…”
Section: Discussionmentioning
confidence: 95%